Utilizing Local Ecosystems as Early Literacy Media: An Analysis of the Implementation of Nature-Based Learning in Early Childhood - Agus; Tuhrotul Faizah; Elyaum farihah; Fauziah Hassan; Sumarno (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Early childhood education is a crucial period in the formation of brain architecture, which forms the foundation for children's language and cognitive development. This study explores how the integration of nature into learning at RA Nawa Kartika VIII Sidolaju transforms the surrounding environment into a dynamic classroom that stimulates the early literacy of children aged 5-6 years. Using qualitative methods with a case study approach, this study describes children's multisensory interactions when manipulating real objects such as soil and plants as a means of constructing knowledge independently. Data were collected through participant observation, in-depth interviews, and documentation. The results revealed that nature-based learning fosters a curiosity-centered learning atmosphere, where children transform from passive recipients of information to active observers. Direct exploration activities create strong episodic memories, making it easier for children to construct narratives of experiences with a more coherent structure and richer vocabulary. Although the natural environment provides abundant stimuli, the success of this process depends heavily on the role of teachers as facilitators who guide free exploration into meaningful learning experiences. This study concludes that utilizing local ecosystems is an effective pedagogical innovation for strengthening children's literacy foundations through concrete and contextual experiences.